ADHESIVE WEAR PERFORMANCE OF CFRP MULTILAYERED POLYESTER COMPOSITES UNDER DRY/WET CONTACT CONDITIONS - D., Danaelan; B. F., Yousif (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
The tribo-performance of a new engineering composite material based on coconut fibers was investigated. In this work, coconut fibers reinforced polyester (CFRP) composites were developed. The tribo-experiments were conducted by using pin-on-disc machine under dry and wet sliding contact condition against smooth stainless steel counterface. Worn surfaces were observed using optical microscope. Friction coefficient and specific wear rate were presented as a function of sliding distance (0-0.6 km) at different sliding velocities (0.1-0.28 m/s). The effect of applied load and sliding velocity was evaluated. The results showed that all test parameters have significant influence on friction and wear characteristics of the composites. Moreover, friction coefficient increased as the normal load and speed increased, the values were about 0.7-0.9 under dry contact condition. Meanwhile, under wet contact condition, there was a great reduction in the friction coefficient, i.e. the values were about 0.1-0.2. Furthermore, the specific wear rates were found to be around 2-4 (10-3) mm(3)/Nm under dry contact condition and highly reduced under wet condition. In other words, the presence of water as cleaner and polisher assisted to enhance the adhesive wear performance of CFRP by about 10%. The images from optical microscope showed evidence of adhesive wear mode with transition to abrasive wear mode at higher sliding velocities due to third body abrasion. On the other hand, optical images for wet condition showed less adhesive wear and smooth surfaces.